A conductive silver paste containing supported Ag-MOF and preparation method thereof

By loading ultrafine acrylate in Ag-MOF material, the load-loaded Ag-MOF conductive silver paste filler is solved, and the existing conductive silver paste has been achieved with high efficiency and excellent printing performance.

CN115512872BActive Publication Date: 2025-03-21JIANGXI JIAYIN SCI & TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211225472.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-09
Publication Date
2025-03-21
Estimated Expiration
2042-10-09

AI Technical Summary

Technical Problem

While improving the conductivity and printing performance, the existing conductive silver paste is difficult to meet the requirements of dispersion and conductivity at the same time, and there is also the problem of high body resistance.

Method used

The loaded Ag-MOF material is used as the filler for conductive silver paste. By loading ultrafine acrylate in Ag-MOF, it combines its good contact action and high stability, high conductivity, good dispersion and printing properties of Ag-MOF.

Benefits of technology

It realizes the effect of simple components of conductive silver paste, convenient preparation process, excellent printing performance, perfect line shape and excellent conductivity, reducing contact resistance and improving stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115512872B_ABST
    Figure CN115512872B_ABST
Patent Text Reader

Abstract

The invention discloses a conductive silver paste containing a supported Ag-MOF and a preparation method thereof. By using a supported Ag-MOF material loaded with ultrafine acrylate as a filler of the conductive silver paste, the supported filler can give full play to the good contact effect of acrylate, reduce contact resistance, and also have the high stability, high conductivity, good dispersibility and printing performance of Ag-MOF. Using Ag-MOF material as a carrier to load ultrafine acrylate can combine the advantages of the two, make up for the shortcomings of a single material, and achieve the technical purpose of "1+1>2", and the conductive silver paste prepared has the advantages of simple components, convenient preparation process, excellent printing performance, perfect linear shape and excellent conductive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a conductive silver paste for a crystalline silicon solar cell, in particular to a conductive silver paste containing a supported Ag-MOF and a preparation method thereof, belonging to the technical field of conductive silver paste for solar cells. Background Art

[0002] Clean energy is gaining more and more attention. Its advantage is that it does not pollute the atmosphere. In the future, clean energy will gradually occupy an increasingly important position in the energy field, and even replace traditional fossil energy. As one of the important members of clean energy, solar energy has been widely studied and applied. Conductive silver paste for crystalline silicon solar cells has become the mainstream of the market due to its superior conductive properties, relatively low cost, and simple preparation process. Conductive silver paste for solar cells must first meet good conductive properties and printing properties. Many researchers are committed to improving these two properties of conductive silver paste and have adopted countless methods.

[0003] Conductive silver paste is generally composed of three main parts: silver powder, glass powder and organic carrier, so these three components have become the main research objects of conductive silver paste. After continuous and in-depth research by many researchers, the comprehensive performance of conductive silver paste has been greatly improved. In particular, the application of suitable fillers in the paste can make a major breakthrough in the printing performance and electrical performance of the product, which puts high demands on the fillers. The fillers need to meet good dispersibility and conductivity at the same time. In addition, the filling needs to be improved and the body resistance needs to be reduced. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides a conductive silver paste containing a loaded Ag-MOF and a preparation method thereof. By using a loaded Ag-MOF material loaded with ultrafine acrylate as a filler of the conductive silver paste, the loaded filler can give full play to the good contact effect of acrylate, reduce contact resistance, and also have the high stability, high conductivity, good dispersibility and printing performance of Ag-MOF. Using Ag-MOF material as a carrier to load ultrafine acrylate can combine the advantages of the two, make up for the deficiencies of a single material, and then prepare a conductive silver paste with simple components, convenient preparation process, excellent printing performance, perfect linear shape and excellent conductive performance.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is specifically described as follows:

[0006] According to a first embodiment of the present invention, a conductive silver paste containing supported Ag-MOF is provided:

[0007] A conductive silver paste containing supported Ag-MOF, comprising: 80-92wt% (preferably 85-90wt%) of silver powder, 1-7wt% (preferably 2-5wt%) of glass powder, 5-15wt% (preferably 7-12wt%) of organic carrier and 0.1-10wt% (preferably 0.5-8wt%) of supported Ag-MOF.

[0008] The organic carrier of the present invention is an organic carrier conventionally used in silver paste, and the present invention does not impose any special restrictions on the selection of the organic carrier.

[0009] Preferably, the supported Ag-MOF is an Ag-MOF loaded with acrylate. The acrylate is selected from one or more of zinc acrylate, copper acrylate, and nickel acrylate. The Ag-MOF is prepared by a hydrothermal method using silver nitrate and terephthalic acid as raw materials.

[0010] Preferably, the loading amount of acrylate in the supported Ag-MOF is 20-50 wt %, preferably 25-45 wt %, and more preferably 30-40 wt %.

[0011] Preferably, the Ag-MOF is a porous spherical structure with an average particle size of 0.3-3 μm, preferably 0.5-2.5 μm, and more preferably 0.8-2 μm.

[0012] Preferably, the acrylate is in the form of spherical nanoparticles with an average particle size of 5-150 nm, preferably 10-100 nm, and more preferably 20-80 nm.

[0013] Preferably, the glass powder is lead-containing glass powder, and the particle size of the lead-containing glass powder is D50<5μm, preferably the particle size of the lead-containing glass powder is D50<4μm, and more preferably the particle size of the lead-containing glass powder is D50<3μm.

[0014] Preferably, the viscosity of the conductive silver paste is 50-150 kcps@50 rpm, preferably 60-120 kcps@50 rpm, and more preferably 70-100 kcps@50 rpm. The fineness of the conductive silver paste is less than 10 μm, preferably less than 8 μm, and more preferably less than 6 μm. The solid content of the conductive silver paste is 85-96 wt %, preferably 88-94 wt %, and more preferably 90-92 wt %.

[0015] According to a second embodiment of the present invention, a method for preparing a conductive silver paste containing supported Ag-MOF is provided:

[0016] A method for preparing a conductive silver paste containing supported Ag-MOF or a method for preparing a conductive silver paste containing supported Ag-MOF according to the first embodiment, the method comprising:

[0017] 1) Preparation of supported Ag-MOF: A silver source (eg, silver nitrate) and terephthalic acid are dissolved in deionized water to obtain a suspension, and the suspension is then transferred to a reactor and heated for reaction to obtain Ag-MOF.

[0018] 2) First, silver powder, glass powder, organic carrier and supported Ag-MOF are uniformly mixed according to a proportion to obtain a premixed slurry, and then the premixed slurry is centrifuged to obtain a mixed slurry.

[0019] 3) Grinding the obtained mixed slurry, and filtering to obtain the target conductive silver paste.

[0020] Preferably, in step 2), the rotation speed of the centrifugal treatment is 800-1200 r / min, preferably 900-1100 r / min, and the time of the centrifugal treatment is 30-90 s, preferably 40-70 s.

[0021] Preferably, in step 3), the grinding treatment is to grind the mixed slurry with a three-roll grinder for 3-15 times, preferably 4-12 times, and more preferably 5-10 times.

[0022] Preferably, in step 3), the pore size of the filter during the filtration treatment is 200-600 mesh, preferably 250-500 mesh, and more preferably 300-450 mesh.

[0023] Preferably, in step 2), the mass ratio of silver powder, glass powder, organic carrier and supported Ag-MOF added is 80-92:1-7:5-15:0.1-10, preferably 85-90:2-5:7-12:0.5-8wt%.

[0024] Preferably, the silver powder is coated silver powder, and the purity of the silver powder in the coated silver powder is 98-99.9wt%, preferably 98.5-99.8wt%, and more preferably 99-99.7wt%. The content of the coating agent in the coated silver powder is 0.1-2wt%, preferably 0.2-1.8wt%, and more preferably 0.3-1.5wt%. The particle size of the coated silver powder is D50=0.8-2.5μm, preferably D50=1-2.2μm, and more preferably D50=1.2-2μm. The coating agent can be any coating agent conventionally used for silver powder in silver paste production, and the present invention does not make any special restrictions.

[0025] Preferably, the particle size of the lead-containing glass powder is D50<5μm, preferably D50<4μm, and more preferably D50<3μm. The lead-containing glass powder of the present invention is a commercially available glass powder conventionally used for silver paste, and is not particularly limited in the present invention.

[0026] Preferably, the Ag-MOF is a porous spherical structure with an average particle size of 0.3-3 μm, preferably 0.5-2.5 μm, and more preferably 0.8-2 μm.

[0027] In the prior art, suitable fillers are one of the important factors in changing the performance of conductive silver paste. Generally, fillers need to satisfy good dispersibility and conductivity at the same time, and also need to improve filling and reduce bulk resistance. Acrylate can be used as a filler for conductive silver paste because it has good contact effect and can reduce contact resistance. However, acrylate is unstable and easy to aggregate and absorb water, so when it is used as a filler for conductive silver paste, the performance improvement of conductive silver paste is limited.

[0028] In the present invention, Ag-MOF material is used as a carrier to load ultrafine acrylate, thereby obtaining a loaded Ag-MOF conductive silver paste filler, which has both the good contact property of acrylate and can reduce contact resistance, and the high stability, conductivity, good dispersibility and excellent printing performance of Ag-MOF material. That is to say, by loading ultrafine acrylate in Ag-MOF material, the loaded filler obtained can combine the advantages of acrylate and Ag-MOF material at the same time, and make up for the deficiency of a single material, and add it to the conductive silver paste, which has good dispersibility and lubrication, and the conductive silver paste using this filler has good printing performance and excellent electrical properties.

[0029] In the present invention, the acrylate is selected from one or more of nano-acrylate zinc, nano-acrylate copper, and nano-acrylate nickel. They can improve the contact effect of silver paste and reduce the body resistance of silver wire. The nano-scale acrylate used must be simple to prepare, easy to obtain, and the metal activity is stronger than silver.

[0030] In the present invention, the loading amount of acrylate in the supported Ag-MOF is 20-50wt%. When the loading amount is too low (e.g., less than 20wt%), the enhancement effect on the slurry contact is weak, and when the loading amount is too high (e.g., greater than 50%), the conductivity of the silver wire after metallization will be significantly reduced (both have been verified by experiments, and the reduction is about 20% and 25% respectively).

[0031] In the present invention, the glass powder is lead-containing glass powder, which has a low melting point, good wettability, and uniform distribution, and its etching effect on the silicon nitride layer on the surface of crystalline silicon is easy to control.

[0032] In the present invention, the organic carrier is a system with ethyl cellulose as the resin, which has good lubrication and film-forming properties and is easy to prepare products with different molecular weights to meet customer needs.

[0033] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0034] 1: The present invention adopts Ag-MOF material as a carrier to load ultrafine acrylate, thereby obtaining a loaded Ag-MOF conductive silver paste filler. The loaded filler can give full play to the good contact effect of acrylate and reduce the contact resistance. At the same time, it also has the high stability, high conductivity, good dispersibility and printing performance of Ag-MOF, achieving the technical purpose of "1+1>2".

[0035] 2: The supported Ag-MOF filler of the present invention combines the advantages of Ag-MOF material and acrylate, and also makes up for the shortcomings of a single material. The conductive silver paste prepared has the advantages of simple components, convenient preparation process, excellent printing performance, perfect linear shape and excellent conductive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a 3D line graph of the conductive silver paste prepared in Example 1 of the present invention.

[0037] Figure 2 This is a 3D line graph of the conductive silver paste prepared in Example 2 of the present invention.

[0038] Figure 3 This is a 3D line graph of the conductive silver paste prepared in Example 3 of the present invention.

[0039] Figure 4 This is a 3D line graph of the conductive silver paste prepared in Comparative Example 1 of the present invention.

[0040] Figure 5 It is a 3D line diagram of a battery cell having the conductive silver paste prepared in Example 1 of the present invention.

[0041] Figure 6 It is a 3D line diagram of a battery cell having the conductive silver paste prepared in Example 2 of the present invention.

[0042] Figure 7 It is a 3D line diagram of a battery cell having the conductive silver paste prepared in Example 3 of the present invention.

[0043] Figure 8 It is a 3D line diagram of a battery cell having the conductive silver paste prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.

[0045] A method for preparing a conductive silver paste containing supported Ag-MOF, the method comprising:

[0046] 1) Preparation of supported Ag-MOF: A silver source (e.g., silver nitrate) and terephthalic acid are dissolved in deionized water to obtain a suspension, and the suspension is then transferred to a reactor and sealed, and then heated to 200-400° C. for reaction for 1-5 days. The reaction product is cooled and dried to obtain Ag-MOF.

[0047] 2) First, silver powder, glass powder, organic carrier and supported Ag-MOF are uniformly mixed according to a proportion to obtain a premixed slurry, and then the premixed slurry is centrifuged to obtain a mixed slurry.

[0048] 3) Grinding the obtained mixed slurry, and filtering to obtain the target conductive silver paste.

[0049] Preferably, in step 2), the rotation speed of the centrifugal treatment is 800-1200 r / min, preferably 900-1100 r / min, and the time of the centrifugal treatment is 30-90 s, preferably 40-70 s.

[0050] Preferably, in step 3), the grinding treatment is to grind the mixed slurry with a three-roll grinder for 3-15 times, preferably 4-12 times, and more preferably 5-10 times.

[0051] Preferably, in step 3), the pore size of the filter during the filtration treatment is 200-600 mesh, preferably 250-500 mesh, and more preferably 300-450 mesh.

[0052] Preferably, in step 2), the mass ratio of silver powder, glass powder, organic carrier and supported Ag-MOF added is 80-92:1-7:5-15:0.1-10, preferably 85-90:2-5:7-12:0.5-8wt%.

[0053] Preferably, the purity of the silver powder in the coated silver powder is 98-99.9wt%, preferably 98.5-99.8wt%, and more preferably 99-99.7wt%. The content of the coating agent in the coated silver powder is 0.1-2wt%, preferably 0.2-1.8wt%, and more preferably 0.3-1.5wt%. The particle size of the coated silver powder is D50=0.8-2.5μm, preferably D50=1-2.2μm, and more preferably D50=1.2-2μm.

[0054] Preferably, the particle size of the lead-containing glass powder is D50<5 μm, preferably the particle size of the lead-containing glass powder is D50<4 μm, and more preferably the particle size of the lead-containing glass powder is D50<3 μm.

[0055] Preferably, the Ag-MOF is a porous spherical structure with an average particle size of 0.3-3 μm, preferably 0.5-2.5 μm, and more preferably 0.8-2 μm.

[0056] Example 1

[0057] Preparation of supported Ag-MOF: 7.2 parts of silver nitrate and 1.44 parts of terephthalic acid were dissolved in 30 ml of deionized water to obtain a suspension, which was then transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene and sealed, and then placed in an oven at 260°C for 96 hours. After the reaction, the product was cooled to room temperature, and the obtained white precipitate was filtered, washed, and dried in an oven at 70°C for 8 hours to obtain Ag-MOF.

[0058] 89.2 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.7wt%, D50 of coated silver powder is 1.6μm), 2.1 parts of lead glass powder (D50<3μm), 8.3 parts of organic carrier, 0.4 parts of supported Ag-MOF (acrylate loading is about 30wt%) are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, the obtained mixed slurry is ground 8 times using a three-roll mill (three-roll milling parameters are set as shown in Table 1), and after grinding, a 400-mesh filter is used for filtering to obtain the target conductive silver paste.

[0059] Table 1

[0060]

[0061]

[0062] Example 2

[0063] Preparation of supported Ag-MOF: same as in Example 1.

[0064] 89.2 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.7wt%, D50 of coated silver powder is 1.6μm), 2.1 parts of lead glass powder (D50<3μm), 8.1 parts of organic carrier, 0.6 parts of supported Ag-MOF (acrylate loading is about 33wt%) are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll grinder is used to grind the obtained mixed slurry 8 times (the roller spacing during each grinding process needs to be set so that the fineness of the slurry gradually decreases until it meets the requirements), and after grinding, a 400-mesh filter screen is used for filtration to obtain the target conductive silver paste. The three-roll grinding parameter settings are the same as those in Example 1

[0065] Example 3

[0066] Preparation of supported Ag-MOF: same as Example 1.

[0067] 89.2 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.7wt%, D50 of coated silver powder is 1.6μm), 2.1 parts of lead glass powder (D50<3μm), 7.9 parts of organic carrier, 0.8 parts of supported Ag-MOF (acrylate loading is about 37wt%) are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll grinder is used to grind the obtained mixed slurry 8 times (the roller spacing during each grinding process needs to be set so that the fineness of the slurry gradually decreases until it meets the requirements), and after grinding, a 400-mesh filter screen is used for filtration to obtain the target conductive silver paste. The three-roll grinding parameter settings are the same as those in Example 1

[0068] Comparative Example 1

[0069] 89.2 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.7wt%, D50 of coated silver powder is 1.6μm), 2.1 parts of lead glass powder (D50<3μm), and 8.7 parts of organic carrier are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (rotation speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll grinder is used to grind the obtained mixed slurry 8 times (the roller spacing during each grinding process needs to be set so that the fineness of the slurry gradually decreases until it meets the requirements). After grinding, a 400-mesh filter screen is used for filtration to obtain the target conductive silver paste. The three-roll grinding parameter settings are the same as those in Example 1

[0070] Comparative Example 2

[0071] 89.2 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.7wt%, D50 of coated silver powder is 1.6μm), 2.1 parts of lead glass powder (D50<3μm), 8.3 parts of organic carrier, 0.4 parts of zinc acrylate are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (rotation speed is 1000r / min, centrifugation time is 50s) to obtain a mixed slurry. Finally, a three-roll grinder is used to grind the obtained mixed slurry 8 times (the roller spacing during each grinding process needs to be set so that the fineness of the slurry gradually decreases until it meets the requirements). After grinding, a 400-mesh filter screen is used for filtration to obtain the target conductive silver paste. The three-roll grinding parameter settings are the same as those in Example 1

[0072] Comparative Example 3

[0073] 89.2 parts of coated silver powder (silver powder purity is 99.9wt%, coating agent content is 0.7wt%, D50 of coated silver powder is 1.6μm), 2.1 parts of lead glass powder (D50<3μm), 8.3 parts of organic carrier, 0.4 parts of Ag-MOF are stirred and mixed to obtain a premixed slurry, and then the premixed slurry is placed in a high-speed centrifugal disperser for centrifugal treatment (speed is 1000r / min, centrifugal time is 50s) to obtain a mixed slurry. Finally, a three-roll grinder is used to grind the obtained mixed slurry 8 times (the roller spacing during each grinding process needs to be set so that the fineness of the slurry gradually decreases until it meets the requirements). After grinding, a 400-mesh filter screen is used for filtration to obtain the target conductive silver paste. The three-roll grinding parameter settings are the same as those in Example 1

[0074] Performance Testing:

[0075] The conductive silver pastes prepared in Examples 1-3 and Comparative Examples 1-3 were printed on crystalline silicon solar cells using a Maxwell screen printer, and then subjected to high-temperature sintering in a sintering furnace. The performance of each cell was tested.

[0076] The electrical performance data of the battery cell is tested using a Berger tester.

[0077] The electrical performance test data is shown in the following table:

[0078]

[0079] The printing line type of the slurry was tested using a Keyence electron microscope:

[0080] The test line type data is shown in the following table:

[0081]

[0082]

Claims

1. A conductive silver paste containing supported Ag-MOF, characterized in that: The conductive silver paste comprises: 80-92 wt% of silver powder, 1-7 wt% of glass powder, 5-15 wt% of organic carrier and 0.1-10 wt% of supported Ag-MOF; The loaded Ag-MOF is an Ag-MOF loaded with acrylate, wherein the loading amount of acrylate in the loaded Ag-MOF is 20-50wt%; the acrylate is selected from one or more of zinc acrylate, copper acrylate, and nickel acrylate; the Ag-MOF is prepared by a hydrothermal method using silver nitrate and terephthalic acid as raw materials; the Ag-MOF is a porous spherical structure with an average particle size of 0.3-3μm; the acrylate is a spherical nanoparticle with an average particle size of 5-150nm; the fineness of the conductive silver paste is less than 10μm.

2. The conductive silver paste according to claim 1, characterized in that: The conductive silver paste comprises: 85-90 wt % of silver powder, 2-5 wt % of glass powder, 7-12 wt % of organic carrier and 0.5-8 wt % of supported Ag-MOF.

3. The conductive silver paste according to claim 1, characterized in that: The loading amount of acrylate in the supported Ag-MOF was 25-45 wt%.

4. The conductive silver paste according to claim 3, characterized in that: The loading amount of acrylate in the supported Ag-MOF was 30-40 wt%.

5. The conductive silver paste according to claim 1, characterized in that: The average particle size of the Ag-MOF is 0.5-2.5 μm; and / or The average particle size of the acrylate is 10-100 nm.

6. The conductive silver paste according to claim 5, characterized in that: The average particle size of the Ag-MOF is 0.8-2 μm; and / or The average particle size of the acrylate is 20-80 nm.

7. The conductive silver paste according to claim 1, characterized in that: The glass powder is lead-containing glass powder.

8. The conductive silver paste according to claim 7, characterized in that: The particle size of the lead-containing glass powder is D50<5μm.

9. The conductive silver paste according to claim 8, characterized in that: The particle size of the lead-containing glass powder is D50<4μm.

10. The conductive silver paste according to claim 9, characterized in that: The particle size of the lead-containing glass powder is D50<3μm.

11. The conductive silver paste according to any one of claims 1 to 10, characterized in that: The viscosity of the conductive silver paste is 50-150 kcps@50 rpm; the solid content of the conductive silver paste is 85-96 wt %.

12. The conductive silver paste according to claim 11, characterized in that: The viscosity of the conductive silver paste is 60-120 kcps@50 rpm; the fineness of the conductive silver paste is less than 8 μm; and the solid content of the conductive silver paste is 88-94 wt %.

13. The conductive silver paste according to claim 12, characterized in that: The viscosity of the conductive silver paste is 70-100 kcps@50 rpm; the fineness of the conductive silver paste is less than 6 μm; and the solid content of the conductive silver paste is 90-92 wt %.

14. A method for preparing a conductive silver paste containing supported Ag-MOF as claimed in any one of claims 1 to 13, characterized in that: The method includes: 1) Preparation of supported Ag-MOF: silver nitrate and terephthalic acid are dissolved in deionized water to obtain a suspension, and then the suspension is transferred to a reactor and heated for reaction to obtain Ag-MOF; acrylate is loaded on the Ag-MOF material to obtain supported Ag-MOF; 2) firstly, silver powder, glass powder, organic carrier and supported Ag-MOF are uniformly mixed according to a proportion to obtain a premixed slurry, and then the premixed slurry is centrifuged to obtain a mixed slurry; 3) Grinding the obtained mixed slurry, and filtering to obtain the target conductive silver paste.

15. The method according to claim 14, characterized in that: The speed of the centrifugal treatment in step 2) is 800-1200 r / min; the time of the centrifugal treatment is 30-90 s; and / or In step 3), the grinding treatment is to grind the mixed slurry 3-15 times using a three-roll grinder; and / or During the filtration process in step 3), the pore size of the filter screen is 200-600 meshes.

16. The method according to claim 15, characterized in that: The speed of the centrifugal treatment in step 2) is 900-1100 r / min; the time of the centrifugal treatment is 40-70 s; and / or In step 3), the grinding treatment is to grind the mixed slurry 4-12 times using a three-roll grinder; and / or In step 3), the pore size of the filter screen during the filtration treatment is 250-500 mesh.

17. The method according to any one of claims 14 to 16, characterized in that: The silver powder is coated silver powder.

18. The method according to claim 17, characterized in that: The purity of the silver powder in the coated silver powder is 98-99.9wt%; the content of the coating agent in the coated silver powder is 0.1-2wt%; and the particle size of the coated silver powder is D50=0.8-2.5μm.

19. The method according to claim 18, characterized in that: The purity of the silver powder in the coated silver powder is 98.5-99.8wt%; the content of the coating agent in the coated silver powder is 0.2-1.8wt%; and the particle size of the coated silver powder is D50=1-2.2μm.

20. The method according to claim 19, characterized in that: The purity of the silver powder in the coated silver powder is 99-99.7wt%; the content of the coating agent in the coated silver powder is 0.3-1.5wt%; and the particle size of the coated silver powder is D50=1.2-2μm.

Citation Information

Patent Citations

  • Ceramic resistive sensor transition layer slurry and preparation method thereof

    CN112635098A

  • Binding agent, organic carrier, front conductive silver paste, preparation method of front conductive silver paste and solar cell

    CN113409987A